Selection Of Profiles In Midship Vessel Structure Operating The Regulations Of The Indonesian Classification Bureau - Palippui, Habibi (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
Ship construction generally consists of two main parts: the hull and the superstructure or deck house. Several factors must be considered in the construction of a ship. Planning the characteristics of the ship's hull, we are also planning the strength and structure of the ship itself. Midship construction is a construction that must have serious attention in calculating the ship structure. In this section, many forces are acting so that there is a relatively large risk of structural failure. One of the world's classification institutions is BKI, which provides rules for selecting structural profiles. Based on these rules, the load on ship sides is 71,284 KN/m2. Load on the ship bottom is 76,795 KN/m2, Deck Load on Deck Superstructures is 32,581 KN/m2, Load on Cargo Deck is 57,330 KN/m2, Load on Inner Bottom is 68,212 KN/m2, Load on Accommodation Decks is 3,981 KN/ m2.